Aplikasi Probiotik Terhadap Pertumbuhan Udang Vanname (Litopenaeus Vannamei) Di Kolam Terpal - Syahyul Putra; Rosmaiti; Agus Putra (CV. SINAR HOWUHOWU, 2026)
White shrimp (Litopenaeus vannamei) is one of the most economically valuable aquaculture commodities. One of the major constraints in vannamei shrimp culture is the decline in water quality caused by the accumulation of feed residues and organic waste, which can inhibit shrimp growth and survival. The application of probiotics is considered an effective approach to improve water quality and enhance shrimp performance. This study aimed to determine the effect of Super Bio AA probiotic supplementation on the growth and survival rate of vannamei shrimp reared in tarpaulin ponds. The study employed a Completely Randomized Design (CRD) consisting of four treatments and three replications. The treatments were: P1 (control without probiotics), P2 (3 g/kg feed), P3 (4 g/kg feed), and P4 (5 g/kg feed). The observed parameters included absolute weight gain, absolute length gain, daily growth rate, survival rate, and water quality. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test. The results showed that probiotic supplementation significantly affected the growth performance and survival of vannamei shrimp. The best performance was obtained in treatment P4, with an absolute weight gain of 0.19 ± 0.01 g, absolute length gain of 1.28 ± 0.31 cm, daily growth rate of 0.45 ± 0.21%, and survival rate of 99.66 ± 3.33%. The improvement in shrimp performance was associated with better feed utilization and improved water quality resulting from probiotic activity. In conclusion, the application of Super Bio AA probiotic at a dosage of 5 g/kg feed was the most effective treatment for enhancing the growth and survival of vannamei shrimp cultured in tarpaulin ponds.